A methods engineering study on Malayan Textile Mills, Inc. - Garces, Mae Margaret (College of Engineering, 2001)
Methods Engineering is a technique used to examine human work in all of its contexts, which lead systematically to the determination of factors that affect the efficiency of a company under study, so as to improve its system. Malayan Textile Mills, Inc. is a manufacturing company that produces knitting yarn from cotton. An area of concern studied by the team was regarding meetings its target production. The company has a daily target production of 6-7,000 kilos a day. However, records show that they only produce only 50 percent of this target. Several factors that affect their production were considere. Analysis made by the team on these factors using work study and methods engineering tools showed that there are three major factors that contribute to the said problem. These are worker absenteeism, lack of supervision and bottlenecking in certain sections of the company. Tour around the plant also gave the team more idea regarding this problem. Further analysis was made on these major causes of not meeting target production. Time study was conducted and results show that there is lack of machines and workers in certain sections in the production process. This guides the team in proposing additional purchase of machines and additional hiring of workers. The number of machines and workers to be added was determined by setting a quota per section of the process. This option was also found to be more effective when there is stricter supervision. Study was also made on frequent worker absenteeism that affects the daily production of the company. The team suggested that additional incentives must be given to workers so as to be more devoted to their work. Setting absence limit must also be implemented to encourage workers to go to work as much as possible. The team evaluated the alternatives generated and suggests such changes to the company. Implementation plan was also provided.